Affirmation, rejection and accommodation: three attitudes to the body (and the world) as implicit religion(s). Issue 1 (2nd January 2022) - Amat Obryk, Matylda
ABSTRACT: Indian philosophy provides a paradigm for understanding human development. It places human development along the line of karma (affirmation), jñāna (rejection) and bhakti (accommodation). Those three attitudes can be observed both chronologically, as they describe the societal progress, and synchronically, as they describe individual ways of coping with the world. In this paper the attitude towards the body is being used as a template for understanding the attitude towards the world.